2014
DOI: 10.1177/0022034514548221
|View full text |Cite
|
Sign up to set email alerts
|

Type IV Collagen is a Novel DEJ Biomarker that is Reduced by Radiotherapy

Abstract: The dental basement membrane (BM) is composed of collagen types IV, VI, VII, and XVII, fibronectin, and laminin and plays an inductive role in epithelial-mesenchymal interactions during tooth development. The BM is degraded and removed during later-stage tooth morphogenesis; however, its original position defines the location of the dentinenamel junction (DEJ) in mature teeth. We recently demonstrated that type VII collagen is a novel component of the inner enamel organic matrix layer contiguous with the DEJ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 31 publications
1
52
0
4
Order By: Relevance
“…In this regard, we hypothesize that ionizing radiation could cause nonselective oxidation of organic components including decarboxylation and finally proteolysis of noncollagenous enamel proteins that were previously present in the interprismatic spaces. This proteolytic mechanism could perhaps occur in a similar way as radiotherapy breaks the links that maintain the ultrastructural organization of organic components in other human tissues [Mitchell and Logan, 1998;Hübner et al, 2005;McGuire et al, 2014a]. On the other hand, we can also hypothesize that such a proteolytic effect could be produced by indirect enzyme activation during or after radiation therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this regard, we hypothesize that ionizing radiation could cause nonselective oxidation of organic components including decarboxylation and finally proteolysis of noncollagenous enamel proteins that were previously present in the interprismatic spaces. This proteolytic mechanism could perhaps occur in a similar way as radiotherapy breaks the links that maintain the ultrastructural organization of organic components in other human tissues [Mitchell and Logan, 1998;Hübner et al, 2005;McGuire et al, 2014a]. On the other hand, we can also hypothesize that such a proteolytic effect could be produced by indirect enzyme activation during or after radiation therapy.…”
Section: Discussionmentioning
confidence: 95%
“…A series of in vitro studies in this context have shown that high doses of ionizing radiation could impair the stability of enamel, dentin, the dentino-enamel junction, human dental pulp, and the periodontal ligament [Pioch et al, 1992;Kielbassa et al, 2006;Konstantonis et al, 2013;McGuire et al, 2014a].…”
mentioning
confidence: 99%
“…With respect to collagen, the authors showed the importance of type IV collagen in the dentin-enamel junction. Reduction of this component may represent biochemical changes and instability of the dentin-enamel junction of irradiated teeth [McGuire et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, type IV collagen loss offers a possible biochemical explanation for the instability observed postradiotherapy in the DEJ. Another region assessed was the coronary dentin, which contains type I collagen and is well-known for the activity of MMP-2 and MMP-9 in processes such as dental erosion and caries [McGuire et al, 2014a].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are few studies in the literature that have evaluated MMP activity in teeth postradiotherapy [McGuire et al, 2014b;Gomes-Silva et al, 2017a, b] and one study that found reduced amounts of collagen type IV [McGuire et al, 2014a]. With regard to the inactivation of MMPs by treatment with protease inhibitors, including green tea or polyphenol epigallocatechin-3-gallate (EGCG) [Kato et al, 2010a[Kato et al, , 2012Buzalaf et al, 2014], chlorhexidine (CHX) [Kato et al, 2010a[Kato et al, , 2012, and sodium fluoride (NaF) , no studies in the literature have been conducted with postradiotherapy teeth.…”
Section: Introductionmentioning
confidence: 99%